2017
DOI: 10.3389/fpls.2017.00804
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Genomic and Transcriptomic Analysis of Five K+ Transporter Gene Families in Soybean Confirm Their Differential Expression for Nodulation

Abstract: Plants have evolved a sophisticated network of K+ transport systems to regulate growth and development. Limited K+ resources are now forcing us to investigate how plant demand can be satisfied. To answer this complex question, we must understand the genomic and transcriptomic portfolio of K+ transporters in plants. Here, we have identified 70 putative K+ transporter genes from soybean, including 29 HAK/KT/KUP genes, 16 genes encoding voltage-gated K+ channels, 9 TPK/KCO genes, 4 HKT genes, and 12 KEA genes. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 76 publications
1
37
0
Order By: Relevance
“…Some studies suggested that some GmKEAs could be localized to the plasma membrane (PM)—e.g. GmKEA2 (Glyma09g39770) and GmKEA5 (Glyma16g32821) ( Chen et al., 2015 ; Rehman et al., 2017 ) ( Table 1 ), although in the former case this unusual PM localization was only predicted ( Rehman et al., 2017 ). For GmKEA5, the localization pattern was based on GFP-tagged GmKEA5 distribution in the transformed onion cells ( Chen et al., 2015 ).…”
Section: Cpa2 Superfamilymentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies suggested that some GmKEAs could be localized to the plasma membrane (PM)—e.g. GmKEA2 (Glyma09g39770) and GmKEA5 (Glyma16g32821) ( Chen et al., 2015 ; Rehman et al., 2017 ) ( Table 1 ), although in the former case this unusual PM localization was only predicted ( Rehman et al., 2017 ). For GmKEA5, the localization pattern was based on GFP-tagged GmKEA5 distribution in the transformed onion cells ( Chen et al., 2015 ).…”
Section: Cpa2 Superfamilymentioning
confidence: 96%
“…The main difference between SOS1A and SOS1B is likely to be in the presence of the cyclic nucleotide-binding domain (PF00027), located in the middle of the C-terminus tail ( Figure 1B ). Such cyclic nucleotide-binding domains are known to bind to the wide range of protein targets, in order to regulate multiple cellular processes ( Shabb and Corbin, 1992 ; LaFranzo et al., 2010 ; Rehmann et al., 2017 ; VanSchouwen et al., 2017 ). SOS1A and SOS1B are both localized to the plasma membrane ( Shi et al., 2000 ; An et al., 2007 ) ( Figure 2 ).…”
Section: Cpa1 Superfamilymentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, [22] demonstrated that HAK5 plays important roles in controlling both the in ux of K + into roots and its transport to the aerial parts of the plant. Two paralogs of our candidate gene (Glyma.02g154100 and Glyma.07g042500) were functionally characterized as being involved in the root uptake of K + in soybean [23,24]. Interestingly, in the work of Dhanapal et al [16], QTLs for K content do overlap with the genomic positions of these HAK5 paralogs.…”
Section: Candidates Genes and Their Functions For Mineral Elements Acmentioning
confidence: 87%
“…In rice, [22] demonstrated that HAK5 plays important roles in controlling both the influx of K + into roots and its transport to the aerial parts of the plant. Two paralogs of our candidate gene (Glyma.02g154100 and Glyma.07g042500) were functionally characterized as being involved in the root uptake of K + in soybean [23,24]. Interestingly, in the work of [16], QTLs for K content do overlap with the genomic positions of these HAK5 paralogs.…”
Section: Candidates Genes and Their Functions For Mineral Elements Acmentioning
confidence: 96%